O10: METFORMIN TREATMENT IMPROVES LYMPHOCYTE METABOLISM IN A MOUSE MODEL OF MAJOR SURGERY. (27th April 2021) - Jones, TF; Gutierrez, A; Arroyo, del; Henson, SM; Ackland, GL
Abstract: Introduction: Lymphopaenia is common after major surgery and associated with poor outcome. T‐lymphocytes restrain damaging innate inflammation. Major surgery impairs T‐lymphocyte metabolism in humans, which promotes lymphopaenia. Metformin is known to improve mitochondrial bioenergetics in models of inflammation. Firstly, we hypothesised that a mouse model of major surgery would demonstrate impaired T‐lymphocyte metabolism and secondly, that metformin treatment in vivo would reverse the phenotype. Method: Male C57Bl/6 mice aged between 8 and 12 weeks were housed in a specific pathogen free environment with free access to food and water. Animals were dosed with either vehicle (phosphate buffered saline, 20 ml/kg) or metformin (250 mg/kg) daily via intraperitoneal injection for four days prior to and after surgery. A partial hepatectomy was performed under isofluorane anaesthesia. Naive littermates were used as controls. All experiments were performed according to the Animals (Scientific Procedures) Act 1986. Splenic T‐lymphocytes were isolated by negative selection using magnetic beads. Mitochondrial bioenergetics were measured using a Seahorse Extracellular Flux analyser. Parametric statistical analysis was performed and a p‐value < 0.05 was chosen to represent significance. Result: T‐lymphocytes demonstrated reduced spare respiratory capacity (SRC, 285 vs 497 %, p=0.004) after surgery compared to naive controls. Metformin treatment in vivo reversed this observation and SRC was comparable to naive (437 vs 497 %, p=0.34). Metformin treatment in vitro increased spare respiratory capacity in T‐lymphocytes from mice after surgery compared to naive (change from untreated, 187 vs 91 %, p=0.03). Conclusion: Perioperative metformin treatment improved T‐lymphocyte metabolism in a mouse model of major surgery. Take‐home message: Metformin is a potential treatment for the lymphocyte metabolic dysfunction observed after surgery.